2019
DOI: 10.1002/hed.26011
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic mapping with SPECT‐CT for evaluation of contralateral drainage in lateralized oropharyngeal cancers using an awake injection technique

Abstract: Background: Risk of contralateral nodal metastases in oropharyngeal squamous cell carcinoma (OPSCC) is currently based on clinical risk factors. We propose lymphatic mapping with single photon emission computed tomography (SPECT-CT) for tumor-specific delineation of lymphatic drainage to guide treatment.Methods: Retrospective review of lymphatic drainage patterns in cT1-2 OPSCC and contralateral cN0 neck with a nonoperative, awake injection of 99 m-Tc sulfur colloid and SPECT-CT. Results: Ten patients were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We observed that in the five patients with N+ disease, the [ 99m Tc]Tc-nanocolloid bypassed the pathologically enlarged nodes and accumulated in the neighboring echelon nodes or at the contralateral side, confirming the results of a recent study. 14 Metastasis formation in lymph nodes prevents tracer accumulation with subsequent drainage and accumulation in the next echelons. 15 This supports the notion that the drainage of the colloid tracer mimics the lymphogenic metastatic route of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that in the five patients with N+ disease, the [ 99m Tc]Tc-nanocolloid bypassed the pathologically enlarged nodes and accumulated in the neighboring echelon nodes or at the contralateral side, confirming the results of a recent study. 14 Metastasis formation in lymph nodes prevents tracer accumulation with subsequent drainage and accumulation in the next echelons. 15 This supports the notion that the drainage of the colloid tracer mimics the lymphogenic metastatic route of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we demonstrate the feasibility of using lymphatic mapping with SPECT-CT to select patients for unilateral neck treatment. Our group has previously reported the feasibility of using this imaging modality to identify lymphatic drainage patterns, and now we demonstrate that treatment of the contralateral neck informed by lymphatic mapping provides acceptable early disease control in the contralateral neck and identifies patients at risk for contralateral nodal drainage [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the injection technique was previously described by our group in an initial feasibly study [ 10 ]. All radiotracer injections were performed awake in the Nuclear Medicine Suite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation